2014
DOI: 10.1353/ajm.2014.0041
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic Forms Representing All Odd Positive Integers

Abstract: Abstract. We consider the problem of classifying all positive-definite integer-valued quadratic forms that represent all positive odd integers. Kaplansky considered this problem for ternary forms, giving a list of 23 candidates, and proving that 19 of those represent all positive odds. (Jagy later dealt with a 20th candidate.) Assuming that the remaining three forms represent all positive odds, we prove that an arbitrary, positive-definite quadratic form represents all positive odds if and only if it represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…In 2014, the author [20] proved a stronger result in a more specific case. If r = 4 and det(Q) is a fundamental discriminant, then every locally represented integer n ≫ D(Q) 2+ǫ is represented.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In 2014, the author [20] proved a stronger result in a more specific case. If r = 4 and det(Q) is a fundamental discriminant, then every locally represented integer n ≫ D(Q) 2+ǫ is represented.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 95%
“…If r = 4 and det(Q) is a fundamental discriminant, then every locally represented integer n ≫ D(Q) 2+ǫ is represented. The bound given in [20] is ineffective (and is related to the possible presence of an L-function with a Siegel zero) and not explicit. However, it is amenable to explicit computations and it was used to prove that x 2 +3y 2 +3yz +3yw +5z 2 +zw +34w 2 , which has D(Q) = N(Q) = 6780, represents all odd positive integers.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…. Obviously, the operators φ p,jp , defined for an arbitrary modular form by the right hand sides of (3.1), (3.2), for distinct primes p commute, and as noticed Improvements on this are possible by [7,8] but have been made effective so far only in few cases, see [13]. At least if the conductor M χ of the character χ is small compared to M these don't give much for our present purpose because of the additional factors coming from oldforms which we computed above.…”
Section: Fourier Coefficients Of Cusp Formsmentioning
confidence: 99%
“…Rouse [21] remarks that at present there is no general algorithm for determining the integers represented by a positive ternary integral quadratic form. Assuming that the three forms in (2) do in fact represent all positive odd integers, Rouse [21] has shown that a positive integral quadratic form in any number of variables is (2, 1)-universal if and only if it represents the positive odd integers 1 to 451 inclusive.…”
Section: Strong 290-theorem If a Positive Integral Quadratic Form Inmentioning
confidence: 99%
“…Rouse's main result [21] was the minimal set of positive odd integers needed for (2, 1)-universality. [4].…”
Section: -Theorem Assuming That the Three Ternary Forms In (2) Rementioning
confidence: 99%